Acute thromboses and occlusions of dual layer carotid stents in endovascular treatment of tandem occlusions - Pfaff, Johannes; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2020)
Purpose: To evaluate the occurrence and risk factors of acute in-stent thrombosis or stent occlusion in patients with tandem occlusions receiving intracranial mechanical thrombectomy and emergent extracranial internal carotid artery stenting with a dual layer carotid stent. - Methods: Multicenter retrospective data collection and analysis of stroke databases of seven comprehensive stroke centers from three European countries. - Results: Overall, 160 patients (mean (SD) age 66 (12) years; 104 men (65%); median (IQR) baseline NIHSS 14 (9-18); IV lysis, n=97 (60.6%)) were treated for a cervical carotid artery occlusion or stenosis using a CASPER stent (MicroVention), and received mechanical thrombectomy for an intracranial occlusion between April 2014 and November 2018. During the procedure or within 72 hours, formation of thrombus and complete occlusion of the CASPER stent was observed in 33/160 (20.8%) and in 12/160 patients (7.5%), respectively. In 25/33 (75.8%) and in 9/12 patients (75%), respectively, this occurred during the procedure. No statistically significant difference was observed between patients with and without thrombus formation with regard to pre-existing long term medication with anticoagulants or intraprocedural administration of heparin, acetylsalicylic acid (ASA), or heparin and ASA. Favorable early neurological outcome was similar in patients with (n=15; 45.5%) and without (n=63; 49.6%) thrombus formation at the CASPER stent. - Conclusion: Acute thrombosis or occlusion of CASPER stents in thrombectomy patients receiving emergent extracranial internal carotid artery stenting for tandem occlusions were observed more often during the procedure than within 72 hours of follow-up, were less frequent then previously reported, and showed no impact on early neurological outcome.
Online issue publication December 20, 2019
Gesehen am 19.02.2020